A critical juncture for synthetic biology: Lessons from nanotechnology could inform public discourse and further development of synthetic biology. (12th June 2018) - Trump, Benjamin D; Cegan, Jeffrey C; Wells, Emily; Keisler, Jeffrey; Linkov, Igor
Abstract : Since its start, synthetic biology has been the subject of intense scrutiny and debate by the public and social scientists. To avoid public resistance and overreaching regulation, the field could learn from how actors in nanotechnology engaged in debate.